Kesadaran Lingkungan & Pengetahuan Produk sebagai Determinan Keputusan Pembelian Skincare Avoskin oleh Gen Z di Kolaka - Susianti, Susianti; Stiadi, Muhamad; Kurniadi, Hanif (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the influence of product knowledge and environmental knowledge on the purchasing decisions of Avoskin products among Generation Z in Kolaka Regency. The research method employed is a quantitative approach with data collection techniques conducted through questionnaires. The population in this study consists of Generation Z individuals aged 15–29 years who have purchased Avoskin products and reside in Kolaka Regency. The research sample comprises 100 respondents selected using the purposive sampling technique. The results of the study indicate that product knowledge and environmental knowledge have a positive and significant impact on the purchasing decisions of Avoskin products among Generation Z in Kolaka Regency. These findings suggest that the higher consumers' understanding of the product and environmental issues, the greater their tendency to choose products that align with their values and preferences